2003
DOI: 10.1038/nm829
|View full text |Cite
|
Sign up to set email alerts
|

A novel viral mechanism for dysregulation of β-catenin in Kaposi's sarcoma–associated herpesvirus latency

Abstract: The Kaposi's sarcoma-associated herpesvirus (KSHV) latency-associated nuclear antigen (LANA) is expressed in all KSHV-associated tumors, including Kaposi's sarcoma (KS) and primary effusion lymphoma (PEL). We found that beta-catenin is overexpressed in both PEL cells and KS tissue. Introduction of anti-LANA small interfering RNA (siRNA) into PEL cells eliminated beta-catenin accumulation; LANA itself upregulated expression of beta-catenin in transfected cells. LANA stabilizes beta-catenin by binding to the neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
268
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 295 publications
(279 citation statements)
references
References 36 publications
8
268
0
2
Order By: Relevance
“…An interaction between GSK-3b and LANA in PELs was previously reported (Fujimuro et al, 2003). GSK-3b was also shown to interact directly with c-Myc both in vitro and in transfected COS-7 cells (Gregory et al, 2003).…”
Section: C-myc and Lana Proteins Are In Complex With Gsk-3b In Pel Cellssupporting
confidence: 52%
See 4 more Smart Citations
“…An interaction between GSK-3b and LANA in PELs was previously reported (Fujimuro et al, 2003). GSK-3b was also shown to interact directly with c-Myc both in vitro and in transfected COS-7 cells (Gregory et al, 2003).…”
Section: C-myc and Lana Proteins Are In Complex With Gsk-3b In Pel Cellssupporting
confidence: 52%
“…Fujimuro et al (2003) found that LANA can induce cell-cycle-dependent nuclear localization of GSK-3b, thereby limiting its activity in the cytoplasm. In addition, most of the nuclear kinase is in an inactive Ser 9 -phosphorylated form while bound to LANA (Hayward et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations